2015
DOI: 10.1007/s00784-015-1657-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral pregabalin for postoperative pain relief after third molar extraction: a randomized controlled clinical trial

Abstract: These findings suggest that pregabalin may be useful to control acute postoperative pain. Adverse effects are known to be reduced at the low pregabalin dose used in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Of note, although pregabalin does not have anti‐inflammatory activity, there is evidence that it attenuates acute postoperative pain , which is consistent with its MoA in affecting neuronal transmission in the pain processing pathways, and also the findings obtained in UVB‐irradiated skin in the present study. Finally, in line with the proven clinical effects of pregabalin and other anti‐epileptic drugs, such as gabapentin and carbamazepine , pregabalin induced a consistent antinociceptive effect on objective and subjective readouts, following (laser) heat stimulation on capsaicin‐irritated skin, which has been hypothesized to resemble neuropathic pain symptoms .…”
Section: Discussionmentioning
confidence: 79%
“…Of note, although pregabalin does not have anti‐inflammatory activity, there is evidence that it attenuates acute postoperative pain , which is consistent with its MoA in affecting neuronal transmission in the pain processing pathways, and also the findings obtained in UVB‐irradiated skin in the present study. Finally, in line with the proven clinical effects of pregabalin and other anti‐epileptic drugs, such as gabapentin and carbamazepine , pregabalin induced a consistent antinociceptive effect on objective and subjective readouts, following (laser) heat stimulation on capsaicin‐irritated skin, which has been hypothesized to resemble neuropathic pain symptoms .…”
Section: Discussionmentioning
confidence: 79%
“…Ineffectiveness of gabapentinoids (i.e. non-indications) is suggested for preemptive and postoperative analgesia [14,15] or radiation-induced mucositis analgesia [43]. A Cochrane review on the analgesic effect of gabapentin in 2010 concluded that although such an effect does exist (when compared to placebo) it is not clinically significant (as compared to standard analgesics) [49].…”
Section: Discussionmentioning
confidence: 99%
“…Four RCTs of good methodological quality (61.5 to 79/100) assessed the usefulness of pregabalin in preemptive analgesia and/or postoperative analgesia before or following third molar surgery [13][14][15] or orthognathic surgery [16]. One double-blind RCT showed that a single postoperative 300 mg dose of pregabalin was superior to ibuprofen or placebo for pain relief following third molar surgery [13].…”
Section: Postoperative Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the duration of the general symptoms varies from these first few hours to 10–15 days later. As a rule, this pain is controlled with oral analgesics, but long-lasting anaesthetics may also be used [ 8 ]. With the mouth, the most commonly used anaesthetic is articaine because of its ideal characteristics: fast onset, potency, and intermediate duration [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%